Gold Mineralisation at the FAT Deposit, Courageous Lake Greenstone Belt, Northwest Territories, Canada - Adam, Marcus A (Scholarship@Western, 2016)
The Courageous Lake Greenstone Belt (CLGB) is hosted in the Yellowknife Supergroup of the Central Slave Province, NWT, Canada: a fertile gold district that includes the former Giant, Con and Lupin orogenic gold mines. The largest deposit in the CLGB is the FAT deposit, which has a proven and probable reserve of 91MT at 2.20gpt gold owned by Seabridge Gold Inc. The FAT deposit differs from other gold deposits in the Yellowknife Supergroup in that deformation and shear textures are intermittent, and where present, deformation does not correlate spatially with mineralisation. The CLGB formed as a volcanic succession that was deposited on a 3218 Ma sodic granitoid gneissic complex. Periodic volcanism commencing at 2660 Ma formed an extrusive cycle of mafic flows to rhyolitic tuffs. The felsic units reach a maximum (post compression) thickness of 1800m proximal to the FAT deposit. Volcanic textures of the rocks hosting the FAT deposit are well preserved sub-aerial lapilli and lesser amounts of ash and bomb tuff. There is periodic intercalation with aqeuously reworked beds. These are overlain by greywacke turbiditic rocks. Three distinct structural/metamorphic events have affected the Courageous Lake Greenstone Belt: 1. compression and vertical tilting of stratigraphy and associated regional dynamothermal metamorphism to mid-greenschist facies commencing at 2592Ma; 2. concurrent discreet thermal metamorphism associated with local granitic intrusions; and 3. late retrograde hydrothermal alteration. Gold is refractory within acicular and rhombic arsenopyrite. Petrography, SIMS, EMP and LA-ICP-MS analysis have defined three arsenopyrite styles of distinct crystal habit with distinct inclusion abundance, Au enrichment and zoning and trace element zoning. The greatest enrichment is in the earliest type of arsenopyrite, attributed to hydrothermal events associated with volcanism. Later, heterogeneous, less enriched arsenopyrite is a result of metamorphic recrystalisation. A strataform quartz body with arsenopyrite and ...